Reforming Economic Growth Model in Vietnam - Huong, Vu Thi Thu (VNU Journal of Science: Policy and Management Studies, 2018)
Abstract: The Communist Party of Vietnam’s (CPV) policy of comprehensive economic renovation and reform of the economic growth model were proposed in two different historical periods. The economic renovation policy was proposed by the 6 th National Congress of the CPV (1986), which defined the focus of a comprehensive reform of the economy for transforming the economy from a self-sufficient economy to a socialist-oriented market one with the State management. Following the economic renovation, the 11 th National Congress of the CPV (2011) proposed the policy of renovation of the growth model and reconstruction of the economy, which was amended by the 12 th National Congress of the CPV (2016). Keywords: Economic reform, development model reform, economy reconstruction, Communist Party of Vietnam